Enhanced photocatalytic degradation of dyes over graphene/Pd/TiO2 nanocomposites: TiO2 nanowires versus TiO2 nanoparticles - Safajou, Hamed; Khojasteh, Hossein; Salavati-Niasari, Masoud; Mortazavi-Derazkola, Sobhan (Journal of colloid and interface science, 2017)
[Display omitted] In this study, at first, TiO2 nanowire was prepared by an alkaline hydrothermal process. In the following, Gr/Pd/TiO2-NPs and Gr/Pd/TiO2-NWs were synthesized by a combination of hydrothermal and photodeposition methods. The properties of as prepared products were characterized using XRD, FT-IR, SEM, DRS, TEM, ICP-OES, EDS and TGA analysis. SEM results confirmed nanodimension structure for all samples. Also the band gap values obtained using DRS technique suggests that all the samples have semiconductor behavior. Using TGA analysis, the amount of graphene loaded onto the powders was confirmed. Photocatalytic degradation of rhodamine B by TiO2-NWs, Gr/Pd/TiO2-NPs and Gr/Pd/TiO2-NWs nanocomposites was compared under ultraviolet light irradiation. Results confirmed that the Gr/Pd/TiO2-NWs composite show the highest photocatalytic activity due to much higher available surface area of TiO2 substrate in nanowire structure. It is expected that the synthesis of the high surface area TiO2 nanowires, facile photodeposition of palladium into its texture, and simple conversion of GO to graphene during hydrothermal process without using strong reducing agents, could be a suitable rote for preparing different types of carbon based TiO2 nanocomposite photocatalysts.